Exercise in Persons with Unilateral Lower-Limb Amputation and Contralateral Limb Knee Injury: A Pilot Study. Issue 1 (January 2019) - Caldwell, Mary E.; Marshall, Benjamin; Semik, Patrick; Huang, Mark E.
Abstract : Introduction: Exercise habits and return to exercise in individuals with lower-limb amputation (LLA) have been reported in up to 11% to 61% of individuals with amputation, but it is unclear if these individuals meet American College of Sports Medicine (ACSM) exercise guidelines and if there are any negative consequences associated with exercise. This pilot study investigated the exercise habits of individuals with unilateral nonvascular LLA to ascertain adherence to ACSM exercise guidelines and any relationships to contralateral (intact)-limb limb knee injuries. Methods: A telephone survey was conducted with 25 individuals (n = 7, female) 22 to 90 years of age (M = 47) with nonvascular unilateral LLAs (2 transmetatarsal/Syme [TM], 13 transtibial [TT], 7 transfemoral [TF], 3 hip disarticulation [HD]) from a university hospital population. Weekly reported exercise before and after amputation (including type, frequency, duration and intensity, based on talk test correlating to intensity) as well as any history of intact-limb knee injuries was obtained. Data were analyzed using χ 2 and one-way analysis of variance tests. Results: Sixty-eight percent met the recommended ACSM guidelines for cardiorespiratory (CR) exercise before amputation and 48% of individuals met CR guidelines after amputation, and, of those, 41.7% reported sustaining intact-limb knee injuries (there were no injuries in those not meeting CR guidelines; P = 0.009). Respondents who met CR guidelines were at significantly higher risk of knee injury ( P = 0.05). Also, those engaged in greater than moderate intensity CR exercise had significantly higher rates of intact knee injury compared with those exercising at low or moderate intensities ( P = 0.01). Conclusions: This pilot study suggests that engaging in an exercise routine at greater than moderate intensity may significantly increase the risk of intact-limb knee injury in individuals with unilateral LLAs. A larger study involving more subjects would be beneficial in clarifying the risk of knee injury from exercise in patients with amputation.